2016
DOI: 10.1007/s00423-016-1442-z
|View full text |Cite
|
Sign up to set email alerts
|

Radiopaque biodegradable stent for duct-to-duct biliary reconstruction in pigs

Abstract: The surgical implantation of radiopaque biodegradable biliary stents in biliary surgery represents a new option for duct-to-duct biliary reconstruction. This technique appears to be feasible and safe and is not associated with any significant biliary complications. The advantage of coated biliary stent use is that it may be visualized using abdominal radiography such as CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Initial animal studies were carried out in the form of a tube to make the thickness of the BS as thin as possible, and it was con rmed that it was completely degraded within six months. [16][17][18] Then, a clinical trial using this tube-type BS in DDLT patients was conducted, and its potential was suggested. 25 However, additional clinical trials using this tube-type BS are not in progress, and the effect and bene t cannot be objectively presented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial animal studies were carried out in the form of a tube to make the thickness of the BS as thin as possible, and it was con rmed that it was completely degraded within six months. [16][17][18] Then, a clinical trial using this tube-type BS in DDLT patients was conducted, and its potential was suggested. 25 However, additional clinical trials using this tube-type BS are not in progress, and the effect and bene t cannot be objectively presented.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, the use of biodegradable stents (BS) in animal models for biliary reconstruction led to good mechanical support properties and biocompatibility. [16][17][18][19][20] Also, BS could serve as carriers for the controlled release of drugs, therefore playing the role of local drug treatment for the prevention of brosis at the anastomotic site. 21 However, there is a chance of stent or tube fracture, which can occur at any point during the biodegradation process.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al (2013) presented a study on the preventative stenting of biliary anastomosis with a completely different type of short stent covered with chemotherapeutics placed through the anastomosis without the need of tensile strength. Tanimoto et al (2016) inserted a stent (made by copolymerization of L-lactide and ε-caprolactone and coated with barium sulphate) into the transected common bile duct and secured it with 6-0 polydioxanone absorbable monofilament suture. This was the only experimental study we found dealing with the preventive trans-anastomotic stenting with a radiologic (computed tomography) follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…16 It has been proved that bile as a degradation medium is more aggressive than PBS and can accelerate the degradation. 17 Therefore, it can be inferred that the degradation of PLLA braided stents in PBS is slower than that in bile and can not truly reflect that in the bile duct. It is necessary to investigate the mechanical properties of PLLA braided stents during degradation in the bile duct environment to more truly evaluate their application prospects in treating severe benign biliary strictures.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the degradation behaviors of PLLA are significantly influenced by the environmental conditions 16 . It has been proved that bile as a degradation medium is more aggressive than PBS and can accelerate the degradation 17 . Therefore, it can be inferred that the degradation of PLLA braided stents in PBS is slower than that in bile and can not truly reflect that in the bile duct.…”
Section: Introductionmentioning
confidence: 99%